A high-temperature-resistant and impact-resistant titanium-aluminum alloy material and a preparation method thereof

CN122959558APending Publication Date: 2026-10-23JIANGSU HAOGUAN ZHONGTITANIUM TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611214508.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-11
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

然而,现有钛铝合金仍存在三大技术瓶颈:其一,高温强度不足,当服役温度超过800℃时,位错攀移与晶界扩散蠕变加剧,导致材料承载能力急剧下降;其二,室温脆性与抗冲击性能差,晶界结合力弱,易发生沿晶断裂,限制了其在冲击载荷工况下的应用;其三,高温抗氧化性能有待提升,高温下氧原子易沿晶界内渗形成疏松的TiO2层,导致基体氧化失效

Benefits of technology

本发明先以钛铝预合金粉末为基体,以邻碳硼烷-聚碳氮烷加合物为新型碳硼前驱体,辅以纳米氢化钛作活化剂经多工艺协同,以实现优异的耐高温性能、抗冲击韧性及抗氧化性能的效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to a high-temperature-resistant and impact-resistant titanium-aluminum alloy material and a preparation method thereof, and belongs to the technical field of titanium-aluminum alloy materials. The titanium-aluminum alloy material is prepared through a multi-step synergic process of solution impregnation coating, low-temperature amorphous packaging, vacuum hot-press sintering, double-stage aging and deep cryogenic tempering, with titanium-aluminum pre-alloy powder as a matrix, with o-carborane-polycarbazane adduct as a carbon-boron precursor, and with nano titanium hydride as an activator. The carbon and boron atoms are uniformly prepositioned through the synergic process of precursor impregnation coating and low-temperature amorphous packaging, and the amorphous shell layer prevents the premature segregation of the carbon and boron atoms. The amorphous shell is slowly crystallized into grain boundary nanoparticles to pin the grain boundary during hot-press sintering. The double-stage aging causes the in-grain precipitation of coherent core-shell nanocages, and the deep cryogenic tempering stabilizes the structure. The above-mentioned synergic process makes the material have excellent high-temperature resistance, impact toughness and oxidation resistance. The titanium-aluminum alloy material prepared by the application has the effects of excellent high-temperature resistance, impact toughness and oxidation resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of titanium-aluminum alloy materials technology, specifically to a high-temperature resistant and impact-resistant titanium-aluminum alloy material and its preparation method. Background Technology

[0002] Titanium-aluminum alloys possess low density, high specific strength, and excellent high-temperature mechanical properties, making them promising candidates for applications in high-temperature structural components such as aerospace engine blades and turbocharger impellers. However, existing titanium-aluminum alloys still face three major technical bottlenecks: First, insufficient high-temperature strength; when service temperatures exceed 800℃, dislocation climb and grain boundary diffusion creep intensify, leading to a sharp decline in the material's load-bearing capacity. Second, poor room-temperature brittleness and impact resistance; weak grain boundary bonding makes them prone to intergranular fracture, limiting their application under impact load conditions. Third, the high-temperature oxidation resistance needs improvement; at high temperatures, oxygen atoms easily diffuse along grain boundaries to form a loose TiO2 layer, leading to matrix oxidation failure.

[0003] To address the aforementioned problems, existing technologies often employ modification methods such as alloying, grain refinement, or ceramic particle reinforcement. However, these methods generally suffer from drawbacks such as uneven distribution of the strengthening phase, poor interfacial bonding, and difficulty in synergistically improving multiple properties. For example, directly adding boride particles easily leads to agglomeration, making it difficult to achieve uniform molecular-level dispersion; single aging treatment results in insufficient stability of the precipitated phase, which is prone to coarsening and failure during high-temperature service. Therefore, developing a titanium-aluminum alloy preparation technology that can simultaneously achieve synergistic strengthening within the grains and at grain boundaries, while also possessing excellent oxidation resistance, is a pressing technical challenge in this field. Summary of the Invention

[0004] The purpose of this invention is to provide a high-temperature resistant and impact-resistant titanium-aluminum alloy material and its preparation method, so as to solve the problems existing in the prior art.

[0005] To solve the above-mentioned technical problems, the present invention provides the following technical solution: a method for preparing a high-temperature resistant and impact-resistant titanium-aluminum alloy material, comprising the following steps: (1) Mix o-carborane and polycarbonate in an argon glove box at a mass ratio of 1:1~3 and stir at 80°C for 4 hours to form a self-made intermediate. After cooling to room temperature, seal for later use. Mix the self-made intermediate, nano-titanium hydride powder and anhydrous tetrahydrofuran at a mass ratio of 1~2:0.1~0.3:10 and ultrasonically disperse for 15 minutes. Then add 40~60 times the mass of the self-made intermediate and pre-alloyed powder after pretreatment. Stir at room temperature for 30 minutes and perform vacuum distillation at 40~50°C to obtain a composite powder with the self-made intermediate and nano-titanium hydride uniformly coated on the surface. (2) Spread the composite powder in the corundum boat and continuously introduce hydrogen-argon mixture. First, purge the air in the furnace at room temperature for 30 minutes to replace the air. Then, raise the temperature to 500℃ at a rate of 2℃ / min and hold for 2 hours. After the holding period, stop heating and let the furnace cool naturally to room temperature to obtain amorphous encapsulation powder. (3) The amorphous encapsulation powder is loaded into the mold, vacuumed, hot-pressed, and demolded to obtain a dense round cake blank. Under the protection of flowing argon, a two-stage aging treatment is carried out to form core-shell nanoparticles inside. The sample that has completed the two-stage aging is directly immersed in a Dewar container filled with liquid nitrogen and cryogenically treated at -196℃ for 2 hours. After the cryogenic treatment is completed, the sample is immediately transferred to 300℃ for tempering. After holding at the temperature for 4 hours, it is taken out and air-cooled to room temperature to obtain a high-temperature resistant and impact-resistant titanium-aluminum alloy material.

[0006] Furthermore, the ortho-carborane in step (1) is an ortho-carborane with a particle size of 50 μm.

[0007] Furthermore, the polycarbonate in step (1) is a polycarbonate with a number average molecular weight of 1000 and a viscosity of 200 mPa·s (25°C).

[0008] Furthermore, the nano-titanium hydride powder mentioned in step (1) is: nano-titanium hydride powder with a particle size of 50 nm.

[0009] Further, step (1) refers to: gas-atomized spherical pre-alloyed powder with a particle size of 15~45μm and an atomic percentage of titanium-48% aluminum-2% chromium-2% niobium.

[0010] Furthermore, the gas flow rate in step (2) is 200 mL / min.

[0011] Furthermore, the hydrogen-argon mixture in step (2) is composed of 5% hydrogen and 95% argon.

[0012] Furthermore, the mold mentioned in step (3) is a graphite mold with an inner diameter of 80 mm.

[0013] Furthermore, the dense round cake blank in step (3) is a dense round cake blank with a diameter of 80 mm and a thickness of 15 mm.

[0014] Furthermore, the diameter of the core-shell nanoparticles in step (3) is 5~20nm.

[0015] Compared with the prior art, the beneficial effects achieved by the present invention are: This invention first uses titanium-aluminum pre-alloyed powder as the matrix, and o-carborane-polycarbazone adduct as a novel carbon-boron precursor, supplemented by nano-titanium hydride as an activator, through multiple processes to achieve excellent high-temperature resistance, impact toughness and oxidation resistance.

[0016] This invention first uses titanium-aluminum pre-alloy powder as a matrix, and an ortho-carborane-polycarbazone adduct as a novel carbon-boron precursor, supplemented with nano-titanium hydride as an activator. Through a multi-step synergistic process of solution impregnation coating, low-temperature amorphous encapsulation, vacuum hot pressing sintering, two-stage aging, and deep cryogenic tempering, a titanium-aluminum alloy with high temperature resistance, impact resistance, and oxidation resistance is obtained. The precursor impregnation coating and low-temperature amorphous encapsulation work together to uniformly pre-place carbon and boron atoms and prevent their premature segregation with an amorphous shell barrier. During hot pressing sintering, the amorphous shell slowly crystallizes into grain boundary nanoparticles, pinning grain boundaries and inhibiting slip. Furthermore, the two-stage aging further precipitates coherent core-shell nanocages within the grains, and deep cryogenic tempering stabilizes its structure. The synergistic effect of intracrystalline nanocages persistently hinders dislocation climb and slip, while grain boundary particles suppress grain boundary diffusion and creep, endowing the material with excellent high-temperature resistance. At the same time, the molecular-level uniform coating ensures the uniform distribution of the stress field of the nanocages. The amorphous encapsulation-hot pressing step forms fine and strong reinforcing particles at the grain boundaries, which synergistically endow the material with excellent impact resistance. Impregnation coating enables the uniform dispersion of boron at the molecular level. Subsequently, amorphous encapsulation and hot pressing sintering fix it in the material in the form of nanocages and grain boundary particles, ensuring that highly dispersed and highly active boron rapidly diffuses to the matrix interface in the early stage of high-temperature oxidation, forming a continuous and dense titanium borosilicate glass layer, which blocks the infiltration of oxygen atoms, giving the material good oxidation resistance. Detailed Implementation

[0017] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0018] To more clearly illustrate the method provided by the present invention, the following embodiments are provided, in which the testing methods for various properties of the titanium-aluminum alloy material produced are as follows: High-temperature resistance test: The titanium-aluminum alloy materials prepared in Examples 1-5 and Comparative Examples 1-4 were tested according to GB / T 2039-2012 "Metallic Materials - Uniaxial Tensile Creep Test Method". The samples were placed in the high-temperature furnace of the creep testing machine, heated to 900℃ at a rate of 10℃ / min, and held at that temperature for 30 min to homogenize the temperature. Then, a constant tensile stress of 300MPa was applied at a rate of 500N / s and maintained. The creep strain percentage was recorded after 100 hours.

[0019] Impact resistance testing: The titanium-aluminum alloy materials prepared in Examples 1-5 and Comparative Examples 1-4 were tested according to GB / T 229-2020 "Metallic Materials - Charpy Pendulum Impact Test Method". The titanium-aluminum alloy was machined into standard Charpy V-notch impact specimens with dimensions of 55mm × 10mm × 10mm, a notch depth of 2mm, and a notch root radius of 0.25mm. The test was conducted at room temperature. The specimen was placed on the impact testing machine support with the notch facing away from the pendulum, and a pendulum with an energy of 300J was used to impact and break the specimen in one strike. The impact absorbed energy was recorded.

[0020] Antioxidation Test: The titanium-aluminum alloy materials prepared in Examples 1-5 and Comparative Examples 1-4 were tested according to the Chinese National Standard GB / T 13303-1991 "Determination of Antioxidation Properties of Steel". The prepared standard samples (20mm × 10mm × 3mm) were ground and polished to a mirror finish, cleaned and dried, and then placed in a high-temperature resistance furnace at 1100℃ for cyclic oxidation experiments. A discontinuous weighing method was used; after every 20 hours of heating, the samples were removed, air-cooled to room temperature, and weighed using an electronic balance with an accuracy of 0.01mg. The total oxidation time was 100 hours. By recording the mass change of the samples, the oxidation rate constant was calculated. The smaller the oxidation rate constant value, the slower and denser the oxide film growth rate, and the stronger the oxidation resistance of the alloy. Example 1

[0021] (1) Atomized spherical pre-alloyed powder with a particle size of 15 μm and an atomic percentage of titanium-48% aluminum-2% chromium-2% niobium was mixed with anhydrous ethanol at a mass ratio of 1:3. After ultrasonic dispersion at 30 kHz for 15 min, the powder was filtered through a 0.45 μm pore size filter membrane. The powder was then placed in a vacuum drying oven and dried at 80 °C and a vacuum degree of -0.1 MPa for 2 h to completely remove the moisture and organic pollutants adsorbed on the powder surface, providing a clean surface for the uniform adsorption of highly active precursors in the future. (2) Mix 50 μm o-carborane with 1000 number average molecular weight and 200 mPa·s (25℃) polycarbonate in an argon glove box at a mass ratio of 1:1. Stir at 300 rpm for 4 h at 80℃ until a self-made intermediate is formed. After cooling to room temperature, seal for later use. Mix the self-made intermediate, 50 nm nano-titanium hydride powder and anhydrous tetrahydrofuran at a mass ratio of 1:0.1:10. Disperse the mixture with ultrasonication at 30 kHz for 15 min. Add 40 times the mass of the self-made intermediate and pre-alloyed powder after pretreatment. Stir at 500 rpm for 30 min at room temperature. Perform vacuum distillation at 40℃ and -0.09 MPa to completely remove the tetrahydrofuran solvent and obtain a composite powder with the self-made intermediate and nano-titanium hydride uniformly coated on the surface. (3) The composite powder was spread evenly in a corundum boat and pushed into a tube furnace. A hydrogen-argon mixture was continuously introduced at a flow rate of 200 mL / min, with hydrogen comprising 5% and argon comprising 95%. The furnace was first purged at room temperature for 30 min to replace the air, and then heated to 500 °C at a rate of 2 °C / min and held for 2 h. After the holding period, the heating was stopped, and the powder was allowed to cool naturally to room temperature in the mixed gas atmosphere to obtain amorphous encapsulated powder. During this process, ortho-borane undergoes thermal decomposition and reacts with the titanium atoms on the powder surface to generate a continuous amorphous boron titanium carbide shell with a thickness of 50 nm in situ; nano-titanium hydride decomposes to release highly active hydrogen, cleaning the powder interface and promoting the densification of the shell. (4) The amorphous encapsulation powder is loaded into a graphite mold with an inner diameter of 80 mm. Graphite paper is placed between the mold cavity and the pressure head to prevent sticking. Then the whole thing is placed in a vacuum hot press furnace. The furnace is evacuated until the gas pressure inside the furnace is no higher than 0.01 Pa. A pre-pressure of 30 MPa is applied. Then the temperature is increased at a rate of 10 °C / min. When the temperature reaches 800 °C, the pressure is increased to 40 MPa and the temperature is continued to rise to 1050 °C. The temperature and pressure are maintained for 1 hour. After the heat preservation is completed, the heating is stopped and the pressure is maintained. The furnace is allowed to cool naturally to room temperature. After demolding, a dense round cake blank with a diameter of 80 mm and a thickness of 15 mm is obtained. During the hot pressing process, the amorphous shell crystallizes and transforms into nanoparticles such as titanium boride and titanium carbide, which are uniformly distributed on the grain boundaries to achieve preliminary pinning. (5) The dense round blank was processed into sample blocks of the required size by wire cutting. Under the protection of flowing argon, a two-stage aging treatment was carried out. The first stage was high-temperature solid solution treatment: the temperature was raised to 1350℃ at a rate of 15℃ / min and held for 30min. Then the sample was quickly taken out of the furnace and quenched with high-pressure argon to allow boron and carbon atoms to fully dissolve back into the γ matrix, forming a supersaturated solid solution and suppressing the precipitation of coarse phases during the cooling process. The second stage was low-temperature precipitation aging: the gas-quenched sample was placed back into the tube furnace that had been heated to 800℃ and held for 6h. After the holding period, it was slowly cooled to 200℃ with the furnace at a rate of 5℃ / min. Then it was taken out and cooled to room temperature in the air. During this low-temperature long-term holding stage, the supersaturated boron and carbon atoms were uniformly precipitated in a coherent manner to form core-shell structured nanoparticles with a core of boron titanium carbide and a shell of boron titanium carbide, with a diameter of 5nm. (6) The sample that has completed the double-stage aging is directly immersed in a Dewar container filled with liquid nitrogen and cryogenically treated at -196℃ for 2 hours. After the cryogenic treatment is completed, the sample is immediately transferred to an air circulation furnace that has been preheated to 300℃ for tempering. After holding at the temperature for 4 hours, it is taken out and air-cooled to room temperature to obtain a high-temperature resistant and impact-resistant titanium-aluminum alloy material. Example 2

[0022] (1) Atomized spherical pre-alloyed powder with a particle size of 25 μm and an atomic percentage of titanium-48% aluminum-2% chromium-2% niobium was mixed with anhydrous ethanol at a mass ratio of 1:3. After ultrasonic dispersion at 30 kHz for 15 min, the powder was filtered through a 0.45 μm pore size filter membrane. The powder was then placed in a vacuum drying oven and dried at 80 °C and a vacuum degree of -0.1 MPa for 2 h to completely remove the moisture and organic pollutants adsorbed on the powder surface, providing a clean surface for the uniform adsorption of highly active precursors in the future. (2) Mix 50 μm o-carborane with 1000 number average molecular weight and 200 mPa·s (25℃) polycarbonate in an argon glove box at a mass ratio of 1:1.5. Stir at 300 rpm for 4 h at 80℃ until a self-made intermediate is formed. After cooling to room temperature, seal for later use. Mix the self-made intermediate, 50 nm nano-titanium hydride powder and anhydrous tetrahydrofuran at a mass ratio of 1.2:0.15:10. Disperse the mixture with ultrasonic at 30 kHz for 15 min. Add 40 to 60 times the mass of the self-made intermediate and pre-alloyed powder after pretreatment. Stir at 500 rpm for 30 min at room temperature. Perform vacuum distillation at 42℃ and -0.09 MPa to completely remove the tetrahydrofuran solvent and obtain a composite powder with the self-made intermediate and nano-titanium hydride uniformly coated on the surface. (3) The composite powder was spread evenly in a corundum boat and pushed into a tube furnace. A hydrogen-argon mixture was continuously introduced at a flow rate of 200 mL / min, with hydrogen comprising 5% and argon comprising 95%. The furnace was first purged at room temperature for 30 min to replace the air, and then heated to 500 °C at a rate of 2 °C / min and held for 2 h. After the holding period, the heating was stopped, and the powder was allowed to cool naturally to room temperature in the mixed gas atmosphere to obtain amorphous encapsulated powder. During this process, ortho-borane undergoes thermal decomposition and reacts with the titanium atoms on the powder surface to generate a continuous amorphous boron titanium carbide shell with a thickness of 65 nm in situ; nano-titanium hydride decomposes to release highly active hydrogen, cleaning the powder interface and promoting the densification of the shell. (4) The amorphous encapsulation powder is loaded into a graphite mold with an inner diameter of 80 mm. Graphite paper is placed between the mold cavity and the pressure head to prevent sticking. Then the whole thing is placed in a vacuum hot press furnace. The furnace is evacuated until the gas pressure inside the furnace is no higher than 0.01 Pa. A pre-pressure of 30 MPa is applied. Then the temperature is increased at a rate of 10 °C / min. When the temperature reaches 800 °C, the pressure is increased to 40 MPa and the temperature is continued to rise to 1050 °C. The temperature and pressure are maintained for 1 hour. After the heat preservation is completed, the heating is stopped and the pressure is maintained. The furnace is allowed to cool naturally to room temperature. After demolding, a dense round cake blank with a diameter of 80 mm and a thickness of 15 mm is obtained. During the hot pressing process, the amorphous shell crystallizes and transforms into nanoparticles such as titanium boride and titanium carbide, which are uniformly distributed on the grain boundaries to achieve preliminary pinning. (5) The dense round blank was processed into sample blocks of the required size by wire cutting. Under the protection of flowing argon, a two-stage aging treatment was carried out. The first stage was high-temperature solid solution treatment: the temperature was raised to 1350℃ at a rate of 15℃ / min and held for 30min. Then the sample was quickly taken out of the furnace and quenched with high-pressure argon to allow boron and carbon atoms to fully dissolve back into the γ matrix, forming a supersaturated solid solution and suppressing the precipitation of coarse phases during the cooling process. The second stage was low-temperature precipitation aging: the gas-quenched sample was placed back into the tube furnace that had been heated to 800℃ and held for 6h. After the holding period, it was slowly cooled to 200℃ with the furnace at a rate of 5℃ / min. Then it was taken out and cooled to room temperature in the air. During this low-temperature long-term holding stage, the supersaturated boron and carbon atoms were uniformly precipitated in a coherent manner to form core-shell structured nanoparticles with a core of boron titanium carbide and a shell of boron titanium carbide, with a diameter of 10nm. (6) The sample that has completed the double-stage aging is directly immersed in a Dewar container filled with liquid nitrogen and cryogenically treated at -196℃ for 2 hours. After the cryogenic treatment is completed, the sample is immediately transferred to an air circulation furnace that has been preheated to 300℃ for tempering. After holding at the temperature for 4 hours, it is taken out and air-cooled to room temperature to obtain a high-temperature resistant and impact-resistant titanium-aluminum alloy material. Example 3

[0023] (1) Atomized spherical pre-alloyed powder with a particle size of 30 μm and an atomic percentage of titanium-48% aluminum-2% chromium-2% niobium was mixed with anhydrous ethanol at a mass ratio of 1:3. After ultrasonic dispersion at 30 kHz for 15 min, the powder was filtered through a 0.45 μm pore size filter membrane. The powder was then placed in a vacuum drying oven and dried at 80 °C and a vacuum degree of -0.1 MPa for 2 h to completely remove the moisture and organic pollutants adsorbed on the powder surface, providing a clean surface for the uniform adsorption of highly active precursors in the future. (2) Mix 50 μm o-carborane with 1000 number average molecular weight and 200 mPa·s (25℃) polycarbazide at a mass ratio of 1:2 in an argon glove box. Stir at 300 rpm for 4 h at 80℃ until a self-made intermediate is formed. After cooling to room temperature, seal for later use. Mix the self-made intermediate, 50 nm nano-titanium hydride powder and anhydrous tetrahydrofuran at a mass ratio of 1.5:0.2:10. Disperse the mixture with ultrasonication at 30 kHz for 15 min. Add 50 times the mass of the self-made intermediate and pre-alloyed powder after pretreatment. Stir at 500 rpm for 30 min at room temperature. Perform vacuum distillation at 45℃ and -0.09 MPa to completely remove the tetrahydrofuran solvent and obtain a composite powder with the self-made intermediate and nano-titanium hydride uniformly coated on the surface. (3) The composite powder was spread evenly in a corundum boat and pushed into a tube furnace. A hydrogen-argon mixture was continuously introduced at a flow rate of 200 mL / min, with hydrogen comprising 5% and argon comprising 95%. The furnace was first purged at room temperature for 30 min to replace the air, and then heated to 500 °C at a rate of 2 °C / min and held for 2 h. After the holding period, the heating was stopped, and the powder was allowed to cool naturally to room temperature in the mixed gas atmosphere to obtain amorphous encapsulated powder. During this process, ortho-borane undergoes thermal decomposition and reacts with the titanium atoms on the powder surface to generate a continuous amorphous boron titanium carbide shell with a thickness of 75 nm in situ; nano-titanium hydride decomposes to release highly active hydrogen, cleaning the powder interface and promoting the densification of the shell. (4) The amorphous encapsulation powder is loaded into a graphite mold with an inner diameter of 80 mm. Graphite paper is placed between the mold cavity and the pressure head to prevent sticking. Then the whole thing is placed in a vacuum hot press furnace. The furnace is evacuated until the gas pressure inside the furnace is no higher than 0.01 Pa. A pre-pressure of 30 MPa is applied. Then the temperature is increased at a rate of 10 °C / min. When the temperature reaches 800 °C, the pressure is increased to 40 MPa and the temperature is continued to rise to 1050 °C. The temperature and pressure are maintained for 1 hour. After the heat preservation is completed, the heating is stopped and the pressure is maintained. The furnace is allowed to cool naturally to room temperature. After demolding, a dense round cake blank with a diameter of 80 mm and a thickness of 15 mm is obtained. During the hot pressing process, the amorphous shell crystallizes and transforms into nanoparticles such as titanium boride and titanium carbide, which are uniformly distributed on the grain boundaries to achieve preliminary pinning. (5) The dense round blank was processed into sample blocks of the required size by wire cutting. Under the protection of flowing argon, a two-stage aging treatment was carried out. The first stage was high-temperature solid solution treatment: the temperature was raised to 1350℃ at a rate of 15℃ / min and held for 30min. Then the sample was quickly taken out of the furnace and quenched with high-pressure argon to allow boron and carbon atoms to fully dissolve back into the γ matrix, forming a supersaturated solid solution and suppressing the precipitation of coarse phases during cooling. The second stage was low-temperature precipitation aging: the gas-quenched sample was placed back into the tube furnace that had been heated to 800℃ and held for 6h. After the holding period, it was slowly cooled to 200℃ with the furnace at a rate of 5℃ / min. Then it was taken out and cooled to room temperature in air. During this low-temperature long-term holding stage, supersaturated boron and carbon atoms were uniformly precipitated in a coherent manner to form core-shell structured nanoparticles with a core of boron titanium carbide and a shell of boron titanium carbide, with a diameter of 15nm. (6) The sample that has completed the double-stage aging is directly immersed in a Dewar container filled with liquid nitrogen and cryogenically treated at -196℃ for 2 hours. After the cryogenic treatment is completed, the sample is immediately transferred to an air circulation furnace that has been preheated to 300℃ for tempering. After holding at the temperature for 4 hours, it is taken out and air-cooled to room temperature to obtain a high-temperature resistant and impact-resistant titanium-aluminum alloy material. Example 4

[0024] (1) Atomized spherical pre-alloyed powder with a particle size of 40 μm and an atomic percentage of titanium-48% aluminum-2% chromium-2% niobium was mixed with anhydrous ethanol at a mass ratio of 1:3. After ultrasonic dispersion at 30 kHz for 15 min, the powder was filtered through a 0.45 μm pore size filter membrane. The powder was then placed in a vacuum drying oven and dried at 80 °C and a vacuum degree of -0.1 MPa for 2 h to completely remove the moisture and organic pollutants adsorbed on the powder surface, providing a clean surface for the uniform adsorption of highly active precursors in the future. (2) Mix 50 μm o-carborane with 1000 number average molecular weight and 200 mPa·s (25℃) polycarbonate in an argon glove box at a mass ratio of 1:2.5. Stir at 300 rpm for 4 h at 80℃ until a self-made intermediate is formed. After cooling to room temperature, seal for later use. Mix the self-made intermediate, 50 nm nano-titanium hydride powder and anhydrous tetrahydrofuran at a mass ratio of 1.8:0.25:10. After ultrasonic dispersion at 30 kHz for 15 min, add 55 times the mass of the self-made intermediate and pre-alloyed powder after pretreatment. Stir at 500 rpm for 30 min at room temperature. Perform vacuum distillation at 48℃ and -0.09 MPa to completely remove the tetrahydrofuran solvent and obtain a composite powder with the self-made intermediate and nano-titanium hydride uniformly coated on the surface. (3) The composite powder was spread evenly in a corundum boat and pushed into a tube furnace. A hydrogen-argon mixture was continuously introduced at a flow rate of 200 mL / min, with hydrogen comprising 5% and argon comprising 95%. The furnace was first purged at room temperature for 30 min to replace the air, and then heated to 500 °C at a rate of 2 °C / min and held for 2 h. After the holding period, the heating was stopped, and the powder was allowed to cool naturally to room temperature in the mixed gas atmosphere to obtain amorphous encapsulated powder. During this process, ortho-borane undergoes thermal decomposition and reacts with the titanium atoms on the powder surface to generate a continuous amorphous boron titanium carbide shell with a thickness of 90 nm in situ; nano-titanium hydride decomposes to release highly active hydrogen, cleaning the powder interface and promoting the densification of the shell. (4) The amorphous encapsulation powder is loaded into a graphite mold with an inner diameter of 80 mm. Graphite paper is placed between the mold cavity and the pressure head to prevent sticking. Then the whole thing is placed in a vacuum hot press furnace. The furnace is evacuated until the gas pressure inside the furnace is no higher than 0.01 Pa. A pre-pressure of 30 MPa is applied. Then the temperature is increased at a rate of 10 °C / min. When the temperature reaches 800 °C, the pressure is increased to 40 MPa and the temperature is continued to rise to 1050 °C. The temperature and pressure are maintained for 1 hour. After the heat preservation is completed, the heating is stopped and the pressure is maintained. The furnace is allowed to cool naturally to room temperature. After demolding, a dense round cake blank with a diameter of 80 mm and a thickness of 15 mm is obtained. During the hot pressing process, the amorphous shell crystallizes and transforms into nanoparticles such as titanium boride and titanium carbide, which are uniformly distributed on the grain boundaries to achieve preliminary pinning. (5) The dense round blank was processed into sample blocks of the required size by wire cutting. Under the protection of flowing argon, a two-stage aging treatment was carried out. The first stage was high-temperature solid solution treatment: the temperature was raised to 1350℃ at a rate of 15℃ / min and held for 30min. Then the sample was quickly taken out of the furnace and quenched with high-pressure argon to allow boron and carbon atoms to fully dissolve back into the γ matrix, forming a supersaturated solid solution and suppressing the precipitation of coarse phases during cooling. The second stage was low-temperature precipitation aging: the gas-quenched sample was placed back into the tube furnace that had been heated to 800℃ and held for 6h. After the holding period, it was slowly cooled to 200℃ with the furnace at a rate of 5℃ / min. Then it was taken out and cooled to room temperature in air. During this low-temperature long-term holding stage, the supersaturated boron and carbon atoms were uniformly precipitated in a coherent manner to form core-shell structured nanoparticles with a core of boron titanium carbide and a shell of boron titanium carbide, with a diameter of 18nm. (6) The sample that has completed the two-stage aging is directly immersed in a Dewar container filled with liquid nitrogen and cryogenically treated at -196℃ for 2 hours. After the cryogenic treatment is completed, the sample is immediately transferred to an air circulation furnace that has been preheated to 300℃ for tempering. After holding at the temperature for 4 hours, it is taken out and air-cooled to room temperature to obtain a high-temperature resistant and impact-resistant titanium-aluminum alloy material. Example 5

[0025] (1) Atomized spherical pre-alloyed powder with a particle size of 45 μm and an atomic percentage of titanium-48% aluminum-2% chromium-2% niobium was mixed with anhydrous ethanol at a mass ratio of 1:3. After ultrasonic dispersion at 30 kHz for 15 min, the powder was filtered through a 0.45 μm pore size filter membrane. The powder was then placed in a vacuum drying oven and dried at 80 °C and a vacuum degree of -0.1 MPa for 2 h to completely remove the moisture and organic pollutants adsorbed on the powder surface, providing a clean surface for the uniform adsorption of highly active precursors in the future. (2) Mix 50 μm o-carborane with 1000 number average molecular weight and 200 mPa·s (25℃) polycarbazide in an argon glove box at a mass ratio of 1:3. Stir at 300 rpm for 4 h at 80℃ until a self-made intermediate is formed. After cooling to room temperature, seal for later use. Mix the self-made intermediate, 50 nm nano-titanium hydride powder and anhydrous tetrahydrofuran at a mass ratio of 2:0.3:10. After ultrasonic dispersion at 30 kHz for 15 min, add 40 to 60 times the mass of the self-made intermediate and pre-alloyed powder after pretreatment. Stir at 500 rpm for 30 min at room temperature. Perform vacuum distillation at 50℃ and -0.09 MPa to completely remove the tetrahydrofuran solvent and obtain a composite powder with the self-made intermediate and nano-titanium hydride uniformly coated on the surface. (3) The composite powder was spread evenly in a corundum boat and pushed into a tube furnace. A hydrogen-argon mixture was continuously introduced at a flow rate of 200 mL / min, with hydrogen comprising 5% and argon comprising 95%. The furnace was first purged at room temperature for 30 min to replace the air, and then heated to 500 °C at a rate of 2 °C / min and held for 2 h. After the holding period, the heating was stopped, and the powder was allowed to cool naturally to room temperature in the mixed gas atmosphere to obtain amorphous encapsulated powder. During this process, ortho-borane undergoes thermal decomposition and reacts with the titanium atoms on the powder surface to generate a continuous amorphous boron titanium carbide shell with a thickness of 100 nm in situ; nano-titanium hydride decomposes to release highly active hydrogen, cleaning the powder interface and promoting the densification of the shell. (4) The amorphous encapsulation powder is loaded into a graphite mold with an inner diameter of 80 mm. Graphite paper is placed between the mold cavity and the pressure head to prevent sticking. Then the whole thing is placed in a vacuum hot press furnace. The furnace is evacuated until the gas pressure inside the furnace is no higher than 0.01 Pa. A pre-pressure of 30 MPa is applied. Then the temperature is increased at a rate of 10 °C / min. When the temperature reaches 800 °C, the pressure is increased to 40 MPa and the temperature is continued to rise to 1050 °C. The temperature and pressure are maintained for 1 hour. After the heat preservation is completed, the heating is stopped and the pressure is maintained. The furnace is allowed to cool naturally to room temperature. After demolding, a dense round cake blank with a diameter of 80 mm and a thickness of 15 mm is obtained. During the hot pressing process, the amorphous shell crystallizes and transforms into nanoparticles such as titanium boride and titanium carbide, which are uniformly distributed on the grain boundaries to achieve preliminary pinning. (5) The dense round blank was processed into sample blocks of the required size by wire cutting. Under the protection of flowing argon, a two-stage aging treatment was carried out. The first stage was high-temperature solid solution treatment: the temperature was raised to 1350℃ at a rate of 15℃ / min and held for 30min. Then the sample was quickly taken out of the furnace and quenched with high-pressure argon to allow boron and carbon atoms to fully dissolve back into the γ matrix, forming a supersaturated solid solution and suppressing the precipitation of coarse phases during the cooling process. The second stage was low-temperature precipitation aging: the gas-quenched sample was placed back into the tube furnace that had been heated to 800℃ and held for 6h. After the holding period, it was slowly cooled to 200℃ with the furnace at a rate of 5℃ / min. Then it was taken out and cooled to room temperature in the air. During this low-temperature long-term holding stage, the supersaturated boron and carbon atoms were uniformly precipitated in a coherent manner to form core-shell structured nanoparticles with a core of boron titanium carbide and a shell of boron titanium carbide, with a diameter of 20nm. (6) The sample that has completed the two-stage aging is directly immersed in a Dewar container filled with liquid nitrogen and cryogenically treated at -196℃ for 2 hours. After the cryogenic treatment is completed, the sample is immediately transferred to an air circulation furnace that has been preheated to 300℃ for tempering. After holding at the temperature for 4 hours, it is taken out and air-cooled to room temperature to obtain a high-temperature resistant and impact-resistant titanium-aluminum alloy material.

[0026] Comparative Example 1 The difference between Comparative Example 1 and Example 3 is that 500 grams of titanium-aluminum pre-alloy powder of the same specifications were taken, and equivalent amounts of commercially available nano-titanium boride powder and nano-titanium carbide powder were directly added according to the final boron-carbon stoichiometric ratio of this invention. The mixture was then dry-mixed in a mixer at 200 rpm for 4 hours. The mixed powder was not coated or encapsulated and was directly loaded into a graphite mold, and sintered to density under the same vacuum hot-pressing conditions as in Example 3 (1050℃, 40MPa, 1h). After sintering, only a single stress-relief annealing at 800℃ for 6 hours was performed, without solution treatment or deep cryogenic treatment.

[0027] Comparative Example 2 The difference between Comparative Example 2 and Example 3 is that step (3) is omitted, and step (4) is changed to: the composite powder is loaded into a graphite mold with an inner diameter of 80 mm, and graphite paper is placed between the mold cavity and the press head to prevent sticking. Then the whole thing is placed in a vacuum hot press furnace, and the vacuum is drawn until the gas pressure in the furnace is no higher than 0.01 Pa. A pre-pressure of 30 MPa is applied, and then the temperature is increased at a rate of 10 °C / min. When the temperature reaches 800 °C, the pressure is increased to 40 MPa, and the temperature is continued to rise to 1050 °C. The temperature and pressure are maintained for 1 hour. After the heat preservation is completed, the heating is stopped, and the pressure is maintained and the furnace is allowed to cool naturally to room temperature. After demolding, a dense round cake blank with a diameter of 80 mm and a thickness of 15 mm is obtained. During the hot pressing process, the amorphous shell crystallizes and transforms into nanoparticles such as titanium boride and titanium carbide, which are uniformly distributed on the grain boundaries to achieve preliminary pinning. The remaining steps are the same as in Example 3.

[0028] Comparative Example 3 The difference between Comparative Example 3 and Example 3 is that the two-stage aging in step (5) and the deep-cryogenic tempering in step (6) are not performed. Instead, conventional annealing at 800°C for 4 hours is performed directly. The remaining steps are the same as in Example 3.

[0029] Comparative Example 4 The difference between Comparative Example 4 and Example 3 is that the ortho-carborane-polycarbazide adduct in step (2) is replaced with an equal mass of polycarbazide and a simple mixture of elemental boron powder (boron powder particle size <1μm), the amount of nano-titanium hydride remains unchanged, and the remaining steps are the same as in Example 3.

[0030] Example of effect Table 1 below shows the performance analysis results of the titanium-aluminum alloy materials used in Examples 1 to 5 and Comparative Examples 1 to 4 of the present invention.

[0031] Table 1

[0032] A comparison of the experimental data on 100-hour creep strain between the examples and comparative examples reveals that the present invention first uses titanium-aluminum pre-alloy powder as the matrix, and ortho-carborane-polycarbazone adduct as a novel carbon-boron precursor, supplemented by nano-titanium hydride as an activator. Through a multi-step synergistic process of solution impregnation coating, low-temperature amorphous encapsulation, vacuum hot pressing sintering, two-stage aging, and deep cryogenic tempering, a titanium-aluminum alloy with high temperature resistance, impact resistance, and oxidation resistance is obtained. The precursor impregnation coating and low-temperature amorphous encapsulation work together to uniformly pre-place carbon and boron atoms and prevent their premature segregation with an amorphous shell barrier. During hot pressing sintering, the amorphous shell slowly crystallizes into grain boundary nanoparticles, pinning grain boundaries and inhibiting slip. Furthermore, the two-stage aging further precipitates coherent core-shell nanocages within the grains, and deep cryogenic tempering stabilizes its structure. The above synergy enables the nanocages within the grains to persistently hinder dislocation climbing. The migration and slippage of grain boundary particles inhibit grain boundary diffusion and creep, giving the material excellent high-temperature resistance. A comparison of the impact absorption energy experimental data from the examples and comparisons reveals that the simultaneous molecular-level uniform coating in this invention ensures a uniform distribution of the stress field in the nanocage. The amorphous encapsulation-hot pressing step forms fine and robust reinforcing particles at the grain boundaries, synergistically giving the material excellent impact resistance. A comparison of the oxidation rate constant experimental data from the examples and comparisons reveals that the impregnation coating in this invention enables uniform molecular-level dispersion of boron. Subsequently, amorphous encapsulation and hot pressing sintering fix it in the material as nanocages and grain boundary particles, ensuring that highly dispersed and highly active boron rapidly diffuses to the matrix interface in the early stages of high-temperature oxidation, forming a continuous and dense titanium borosilicate glass layer that blocks oxygen atom infiltration, giving the material good oxidation resistance.

[0033] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within the present invention. No markings in the claims should be construed as limiting the scope of the claims.

Claims

1. A method for preparing a high-temperature resistant and impact-resistant titanium-aluminum alloy material, characterized in that, Includes the following steps: (1) Mix o-carborane and polycarbonate in an argon glove box at a mass ratio of 1:1~3 and stir at 80°C for 4 hours to form a self-made intermediate. After cooling to room temperature, seal for later use. Mix the self-made intermediate, nano-titanium hydride powder and anhydrous tetrahydrofuran at a mass ratio of 1~2:0.1~0.3:10 and ultrasonically disperse for 15 minutes. Then add 40~60 times the mass of the self-made intermediate and pre-alloyed powder after pretreatment. Stir at room temperature for 30 minutes and perform vacuum distillation at 40~50°C to obtain a composite powder with the self-made intermediate and nano-titanium hydride uniformly coated on the surface. (2) Spread the composite powder in the corundum boat and continuously introduce hydrogen-argon mixture. First, purge the air in the furnace at room temperature for 30 minutes to replace the air. Then, raise the temperature to 500℃ at a rate of 2℃ / min and hold for 2 hours. After the holding period, stop heating and let the furnace cool naturally to room temperature to obtain amorphous encapsulation powder. (3) The amorphous encapsulation powder is loaded into the mold, vacuumed, hot-pressed, and demolded to obtain a dense round cake blank. Under the protection of flowing argon, a two-stage aging treatment is carried out to form core-shell nanoparticles inside. The sample that has completed the two-stage aging is directly immersed in a Dewar container filled with liquid nitrogen and cryogenically treated at -196℃ for 2 hours. After the cryogenic treatment is completed, the sample is immediately transferred to 300℃ for tempering. After holding at the temperature for 4 hours, it is taken out and air-cooled to room temperature to obtain a high-temperature resistant and impact-resistant titanium-aluminum alloy material.

2. The high-temperature resistant and impact-resistant titanium-aluminum alloy material according to claim 1, characterized in that, The ortho-carborane mentioned in step (1) is an ortho-carborane with a particle size of 50 μm.

3. The high-temperature resistant and impact-resistant titanium-aluminum alloy material according to claim 1, characterized in that, The polycarbonate in step (1) is a polycarbonate with a number average molecular weight of 1000 and a viscosity of 200 mPa·s (25°C).

4. The high-temperature resistant and impact-resistant titanium-aluminum alloy material according to claim 1, characterized in that, The nano-titanium hydride powder mentioned in step (1) is: nano-titanium hydride powder with a particle size of 50 nm.

5. The high-temperature resistant and impact-resistant titanium-aluminum alloy material according to claim 1, characterized in that, Step (1) refers to: gas-atomized spherical pre-alloyed powder with a particle size of 15~45μm and an atomic percentage of titanium-48% aluminum-2% chromium-2% niobium.

6. The high-temperature resistant and impact-resistant titanium-aluminum alloy material according to claim 1, characterized in that, The gas flow rate in step (2) is 200 mL / min.

7. The high-temperature resistant and impact-resistant titanium-aluminum alloy material according to claim 1, characterized in that, The hydrogen-argon mixture in step (2) is composed of 5% hydrogen and 95% argon.

8. The high-temperature resistant and impact-resistant titanium-aluminum alloy material according to claim 1, characterized in that, The mold mentioned in step (3) is a graphite mold with an inner diameter of 80 mm.

9. The high-temperature resistant and impact-resistant titanium-aluminum alloy material according to claim 1, characterized in that, The dense round cake blank in step (3) is a dense round cake blank with a diameter of 80 mm and a thickness of 15 mm.

10. The high-temperature resistant and impact-resistant titanium-aluminum alloy material according to claim 1, characterized in that, The diameter of the core-shell nanoparticles in step (3) is 5~20nm.